Sistem Pendukung Keputusan Pemilihan Mobil Rental dengan Menggunakan Metode Topsis (Studi Kasus : CV. Bita Jaya Mandiri) - Sri Mandakini (JUKI : Jurnal Komputer dan Informatika, 2020)
Along with the development of the era of demand, to always be fast in doing everything, I can't be avoided from the name of transportation. Transportation is a necessity for everyone alive. The car is one of the negotiated land transportation that is chosen by the people. People who work in the service sector own various types of cars to meet the needs of society. To get a car that meets expectations, of course, the rental tenant / car rental owner must have information about the car. Of the many car choices we can make decisions based on feelings. However, we had difficulty making a decision. Therefore we need a decision support system to help consumers decide which car to rent based on the criteria they want. TOPSIS is a method that can be used in the decision making process. And the products used are Toyota Cars 2000-2014. This method can be used to determine whether the car will be rented according to the qualifications required or not. This is because the method is a step-by-step assessment, both qualitative and quantitative. And TOPSIS is a method of taking into account the tolerance limits for the validity of various criteria chosen by the decision maker.